Mercy road : a novel - Creel, Ann Howard (Lake Union Publishing, 2019)
In 1917, after Arlene Favier<U+2019>s home burns to the ground, taking her father with it, she must find a way to support her mother and younger brother. If she doesn<U+2019>t succeed, they will all be impoverished. Job opportunities are scarce, but then a daring possibility arises: the American Women<U+2019>s Hospital needs ambulance drivers to join a trailblazing, all-female team of doctors and nurses bound for war-torn France. On the front lines, Arlene and her fellow ambulance drivers work day and night to aid injured soldiers and civilians. In between dangerous ambulance runs, Arlene reunites with a childhood friend, Jimmy Tucker, now a soldier, who opens her heart like no one before. But she has also caught the attention of Felix Brohammer, a charismatic army captain who harbors a dark, treacherous secret. To expose Brohammer means risking her family<U+2019>s future and the promise of love. Arlene must make a choice: stay in the safety of silence or take the greatest chance of her life.